The Effectiveness of Virtual Laboratories in Improving Students’ Self-Confidence and Reducing Practicum Anxiety: A Literature Review - Mirna Wahdaniyati; Eka Puji Astuti; Ermafitriyana Ermafitriyana (Indonesian Journal of Teacher Education, 2025)
Innovation in laboratory learning methods has experienced rapid development. One such innovation is the use of virtual laboratories to support student practicum activities. The use of virtual laboratories allows students to conduct interactive experimental simulations, thus helping them understand practicum procedures before conducting them directly. This study aims to assess the effectiveness of using virtual laboratories in increasing student confidence and reducing anxiety levels during practicums. The method used was a literature review by analyzing various scientific articles relevant to the research topic. Data were collected through a literature search in various scientific papers discussing the use of virtual laboratories and their impact on students' psychological aspects. The results of the study indicate that the use of virtual laboratories provides a safe and repeatable learning environment, allowing students to practice conducting experiments without the risk of equipment damage. This condition helps reduce student difficulty levels, improve understanding, foster self-confidence, and reduce anxiety levels during direct practicums. Thus, virtual laboratories can be an effective alternative learning medium in supporting students' psychological readiness for practicum activities.